Increasing Deformation Energy Absorption of AM Drone Fuselages Using a Low-Density Polymeric Material - Artūras Rasinskis; Arvydas Rimkus; Darius Rudinskas; Šarūnas Skuodis; Viktor Gribniak (Applied Sciences)
This study investigates the potential of low-density polymeric materials to enhance the deformation energy absorption of drone fuselage components manufactured using fused filament fabrication (FFF). Two materials—PLA (polylactic acid) and LW-PLA (lightweight polylactic acid)—were selected based on their accessibility, printability, and prior mechanical characterizations. While PLA is widely used in additive manufacturing, its brittleness limits its suitability for components subjected to accidental or impact loads. In contrast, LW-PLA exhibits greater ductility and energy absorption, making it a promising alternative where weight reduction is critical and structural redundancy is available. To evaluate the structural efficiency, a simplified analysis scenario was developed using a theoretical 300 J collision energy, not as a design condition, but as a comparative benchmark for assessing the performance of various metastructural configurations. The experimental results demonstrate that a stiffening core of the LW-PLA metastructure can reduce the component weight by over 60% while maintaining or improving the deformation energy absorption. Modified prototypes with hybrid internal structures demonstrated stable performances under repeated loading; however, the tests also revealed a buckling-like failure of the internal core in specific configurations, highlighting the need for core stabilization within metastructures to ensure reliable energy dissipation.